2008
DOI: 10.1057/palgrave.imfsp.9450031
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Aggregate Use of IMF Resources—Analytical Approaches and Medium-Term Projections

Abstract: This paper presents two approaches to modeling the use of IMF resources from the General Resources Account in order to gauge whether the recent decline in credit outstanding is a temporary or a permanent phenomenon. The two approaches-the time-series behavior of credit outstanding and a two-stage program selection and access model-yield the same conclusion: the use of IMF resources is likely to decline sharply. Specifically, credit outstanding is projected to decline from an average of SDR 50 billion over 2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Elekdag (2006) finds that both the real interest rate and the world business cycle have the expected and significant effect on the probability of the approval of a SBA. In contrast, Ghosh et al (2007) do not find these variables significant in their estimation of the probability of having a SBA/EFF program.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Elekdag (2006) finds that both the real interest rate and the world business cycle have the expected and significant effect on the probability of the approval of a SBA. In contrast, Ghosh et al (2007) do not find these variables significant in their estimation of the probability of having a SBA/EFF program.…”
mentioning
confidence: 62%
“…Conway 1994, Przeworki and Vreeland 2000, Barro and Lee 2005. More recently, Elekdag (2006) and Ghosh et al (2007) focus on the evolution of IMF credit outstanding through the analysis of the determinants of the establishment of new IMF programs.…”
Section: Introductionmentioning
confidence: 99%
“…But the eligibility of a country itself is not enough to require a loan from the IMF. Comprehensive summaries of the studies regarding the determinants of IMF credit can be found in Sturm, Berger, and de Haan (2005) for the period 1992-1994, Ghosh, Goretti, Joshi, Thomas, and Zalduendo (Ghosh, Goretti, Joshi, Thomas, & Zalduendo, 2007) covering 1996-2006and Moser and Sturm (2011 for the 2005-2010 period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this view, it is reasonable to expect that larger foreign direct investments and banks' financial exposure are negatively correlated with the probability of IMF assistance but, once the endogenous selection has been taken into account, drive larger loans. 19 The set of control variables included in the model was chosen on the ground of the empirical findings of the most relevant literature on IMF lending, and reflects foreign imbalances, the levels of economic development and the relationships with the Fund (Bird, 2007;Ghosh et al, 2008;Steinwand & Stone, 2008). Specifically, we consider the current account balance over GDP (CAB) and an indicator of the level of international reserves in terms of months of imports (RESERVE) as measures of foreign imbalances.…”
Section: Countrymentioning
confidence: 99%